Spectral calibration and validation of the Cross‐track Infrared Sounder on the Suomi NPP satellite. Issue 22 (25th November 2013) - Strow, L. Larrabee; Motteler, Howard; Tobin, David; Revercomb, Henry; Hannon, Scott; Buijs, Henry; Predina, Joe; Suwinski, Lawrence; Glumb, Ronald
<x xml:space="preserve">Abstract</x> [1] The Cross‐track Infrared Sounder (CrIS) radiometric accuracy depends upon accurate frequency calibration. Here we present both the prelaunch calibration of the sensor and the minor modifications needed to this calibration post launch. Particular emphasis is given to ensuring that all nine detectors on each of the three CrIS focal planes are on a common frequency scale with accurate off‐axis apodization corrections. Radiances from the current operational algorithm have a frequency calibration that is stable to 2 ppm, although this work suggests that the CrIS instrument is capable of a frequency calibration stability of better than 1 ppm.